Molecular hydrogen from organic sources in the deep Songliao Basin, P.R. China. (1st May 2022) - Horsfield, Brian; Mahlstedt, Nicolaj; Weniger, Philipp; Misch, David; Vranjes-Wessely, Sanja; Han, Shuangbiao; Wang, Chengshan
Abstract: Free hydrogen detected in the Songke-2 well (Songliao Basin, China) has a strong crustal contribution. Here we evaluate whether the source could be the organic matter in Lower Cretaceous coals and shales, and extend our findings regionally. We could establish the rapid growth of aromatic ring systems, forming hydrogen, methane and pyrobitumen, using high resolution mass spectrometry. Molecular hydrogen is generated after late hydrocarbon gas generation is complete, concluding at Rr = 5.0%. The kinetic parameters of molecular hydrogen formation were constructed by subtracting the hydrogen associated with hydrocarbon formation from the total hydrogen, as measured by extensive open system pyrolysis experiments. This new insight was achieved using a CH4 –H2 stoichiometric balance. Generalised calculations indicate that the yield per unit rock volume closely resembles that of economic shale gas in the Barnett Shale, though storage in organic matrices is unlikely in this depositional setting. While the prolific generation of hydrogen from organic sources appears to be a reality in the Songliao basin, the free H2 in the Songke-2 mudstream coming from this source must most likely have migrated into the basement rocks mainly from lateral equivalents of the Shahezi rather than from the drilled section itself. Highlights: H2 is prolifically generated from overmature organic matter in shales and coals. Its yield per unit rock volume closely resembles that of economic shale gas. H2 is generated after hydrocarbon generation is over, extending to ca. 450 °C subsurface. Our new kinetic model based on CH4 –H2 stoichiometry predicts generation in time and space. Hydrogen trapping is more likely in marine shales than in terrestrially influenced shales.